Your successful real estate career - Edwards, Kenneth W., 1928- (AMACOM, American Management Association, 2007)
This book is updated and expanded with the latest tips, trends, and techniques. It is packed with practical tools and enlightening real-world examples. It gives readers detailed, down-to-earth advice on topics including: winning clients; avoiding typical career mistakes; dealing with difficult clients; using the latest technology to improve efficiency and make more sales and much more.